Ion nose spectral structures observed by the Van Allen Probes. Issue 12 (29th December 2016) - Ferradas, C. P.; Zhang, J.‐C.; Spence, H. E.; Kistler, L. M.; Larsen, B. A.; Reeves, G.; Skoug, R.; Funsten, H.
Abstract: We present a statistical study of nose‐like structures observed in energetic hydrogen, helium, and oxygen ions near the inner edge of the plasma sheet. Nose structures are spectral features named after the characteristic shapes of energy bands or gaps in the energy‐time spectrograms of in situ measured ion fluxes. Using 22 months of observations from the Helium Oxygen Proton Electron instrument onboard Van Allen Probe A, we determine the number of noses observed, and the minimum L shell reached and energy of each nose on each pass through the inner magnetosphere. We find that multiple noses occur more frequently in heavy ions than in H + and are most often observed during quiet times. The heavy‐ion noses penetrate to lower L shells than H + noses, and there is an energy‐magnetic local time (MLT) dependence in the nose locations and energies that is similar for all species. The observations are interpreted by using a steady state model of ion drift in the inner magnetosphere. The model is able to explain the energy and MLT dependence of the different types of nose structures. Different ion charge‐exchange lifetimes are the main cause for the deeper penetration of heavy‐ion noses. The species dependence and preferred geomagnetic conditions of multiple‐nose events indicate that they must be on long drift paths, leading to strong charge‐exchange effects. The results provide important insight into the spatial distribution, species dependence, and geomagnetic conditions under which nose structures occur. Key Points: A statistical study of H+, He+, and O+ nose structures observed by the ECT‐HOPE mass spectrometer on board the Van Allen Probes is performed Multiple‐nose structures are preferentially observed in heavy ions and during low activity levels The dependence of nose structures on energy, L, and MLT is generally consistent with a simple model of ion drift and charge‐exchange losses